Congenital heart disease mortality in Spain during a 10 year period (2003-2012) - Javier Pérez-Lescure Picarzo; Margarita Mosquera González; Pello Latasa Zamalloa; David Crespo Marcos (Elsevier, 2018)
Introduction and objectives: Congenital heart disease is a major cause of infant mortality in developed countries. In Spain, there are no publications at national level on mortality due to congenital heart disease. The aim of this study is to analyse mortality in infants with congenital heart disease, lethality of different types of congenital heart disease, and their variation over a 10-year period. Methods: A retrospective observational study was performed to evaluate mortality rate of children under one year old with congenital heart disease, using the minimum basic data set, from 2003 to 2012. Mortality rate and relative risk of mortality were estimated by Poisson regression. Results: There were 2,970 (4.58%) infant deaths in a population of 64,831 patients with congenital heart disease, with 73.8% of deaths occurring during first week of life. Infant mortality rate in patients with congenital heart disease was 6.23 per 10,000 live births, and remained constant during the 10-year period of the study, representing 18% of total infant mortality rate in Spain. The congenital heart diseases with highest mortality rates were hypoplastic left heart syndrome (41.4%), interruption of aortic arch (20%), and total anomalous pulmonary drainage (16.8%). Atrial septal defect (1%) and pulmonary stenosis (1.1%) showed the lowest mortality rate. Conclusions: Congenital heart disease was a major cause of infant mortality with no variations during the study period. The proportion of infants who died in our study was similar to other similar countries. In spite of current medical advances, some forms of congenital heart disease show very high mortality rates. Resumen: Introducción y objetivos: Las cardiopatías congénitas suponen una de las principales causas de mortalidad infantil en países desarrollados. En España no hay publicaciones sobre mortalidad de las cardiopatías congénitas a nivel nacional. El objetivo del estudio es determinar la tasa de mortalidad infantil de las cardiopatías congénitas, así como la letalidad de las distintas cardiopatías, durante un periodo de 10 años. Material y métodos: Estudio observacional retrospectivo utilizando el conjunto mínimo básico de datos de 2003 a 2012 en niños ingresados con diagnóstico de cardiopatía congénita. Se realiza un análisis descriptivo de los pacientes y se calcula la tasa de mortalidad y los riesgos relativos de mortalidad mediante regresión de Poisson. Resultados: Fallecieron 2.970 menores de un año sobre una población de 64.831 pacientes con cardiopatías congénitas (4,58%). El 73,8% fallecieron la primera semana de vida. La tasa de mortalidad infantil en niños con cardiopatías congénitas fue de 6,23 por 10.000 nacidos vivos, cifra que se mantuvo constante a lo largo de los 10 años estudiados y que supone el 18% de la mortalidad infantil total. Las cardiopatías con mayor letalidad fueron el síndrome del corazón izquierdo hipoplásico (41,4%), la interrupción del arco aórtico (20%) y el drenaje venoso pulmonar anómalo total (16,8%), y las de menor letalidad la comunicación interauricular (1%) y la estenosis pulmonar (1,1%). Conclusiones: Las cardiopatías congénitas constituyen una causa importante de mortalidad infantil, que no ha presentado variaciones importantes durante el tiempo de estudio. La proporción de niños que fallecen es similar a la de los países de nuestro entorno. Pese a los actuales avances, algunas cardiopatías presentan letalidad elevada.